2005
DOI: 10.1017/s0001924000005200
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent developments in flow control

Abstract: This paper reviews and highlights recent developments of certain aspects of flow control concerned with reducing the drag of, and delaying flow separation on, wings and bodies over which the flow is turbulent. The study is restricted to devices that extend beyond the viscous sub-layer but are on a smaller scale than geometric features of the aircraft (e.g. wing chord).The review is mainly concerned with developments within the UK, although significant developments in other countries are discussed.The review di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 54 publications
9
58
1
Order By: Relevance
“…In Lin's review [3] on the low-profile vortex generator, it was mentioned that MVG could alleviate the flow distortion in compact ducts to some extent and control boundary layer separation due to the adverse pressure gradients. Similar comments were made in the review by Ashill et al [4].…”
Section: Introductionsupporting
confidence: 72%
“…In Lin's review [3] on the low-profile vortex generator, it was mentioned that MVG could alleviate the flow distortion in compact ducts to some extent and control boundary layer separation due to the adverse pressure gradients. Similar comments were made in the review by Ashill et al [4].…”
Section: Introductionsupporting
confidence: 72%
“…In recent years, as our knowledge of the (vortical) flow structures associated with 3-D SCBs has matured, researchers have begun to compare these devices with vortex generators. In one such study, Colliss et al [9] found that the strength of the vortices produced by a 3-D SCB is of the same order of magnitude as those of vortex generators (as reported by Ashill et al [1]), when expressed in terms of the non-dimensional circulation parameter /(u τ h) (where u τ is the local uncontrolled friction velocity and h is the SCB or vortex generator height). However, Colliss et al [9] also explain that quantifying the 'strength' of the vortices is not always trivial: as the existence of strong shear flows, in which the vortices are embedded, can make it difficult to extract the contribution to of the vortex itself.…”
Section: Comparisons With Other Supersonic Flow Control Strategiesmentioning
confidence: 67%
“…Broadly speaking, a glance through the relevant literature from the past two decades reveals that studies of SCBs fall into one of the two categories: (1) Investigations that consist of parametric studies and/or optimisation; and (2) Investigations that probe the detailed flow physics produced by SCBs in controlled environments. In this review article, we will draw together the results from studies of both types.…”
Section: Scopementioning
confidence: 99%
See 2 more Smart Citations